BindingDB Entry 50001734: Total Syntheses of Lobaric Acid and Its Derivatives from the Antarctic Lichen Stereocaulon alpinum. - BindingDB (BindingDB, 2020)
Small molecule binding data for protein Protein-tyrosine phosphatase 1B, Uniprot A8K3M3 and P18031